Fluid Viscoelasticity Drives Self-Assembly of Particle Trains in a Straight Microfluidic Channel - Francesco Del Giudice (Physical Review Applied, 2018)
Strings of equally spaced particles (particle train) are tremendously important in a variety of microfluidic applications. By using inertial microfluidics, particle trains can be formed near the channel walls. However, the high particle rotation and large local shear gradient near the microchannel walls can lead to blurred images and cell damage, thus negatively affecting applications related to flow cytometry. To address this challenge, we demonstrate that adding a tiny amount of hyaluronic acid biopolymer to an aqueous suspension drives self-assembly of a particle train on the centerline of a square-shaped straight microchannel, with a throughput up to approximately 2400 particles/s. The fraction of equally spaced particles increases by increasing the volumetric flow rate and the distance from the channel inlet. Numerical simulations corroborate the experimental observations and, together with a simple qualitative argument on the particle train stability, shed insights on the underlying mechanism leading to particle ordering.